Exploring AI-personalized visualization of the safe place in virtual reality versus imagination of the safe place for stress, burnout, and relaxation in psychotherapists: a case series - Wollweber, Viktoria; Pfannerstill, Franziska; Probst, Thomas (Frontiers in Digital Health, 2025)
ObjectivesPsychotherapists face substantial occupational stress and emotional demands placing them at risk of burnout, yet interventions aimed at enhancing their well-being remain understudied. This case series explored the effectiveness of a brief relaxation intervention comparing the traditional safe place imagination exercise with a virtual reality (VR) adaptation. The VR adaptation comprised a personalized visualization of the safe place by artificial intelligence (AI). The exploratory research questions investigated how both interventions would influence relaxation, burnout and stress over the course of the study and whether VR would yield different effects than imagination. Further, the roles of imagery ability and presence were explored.MethodsFive psychotherapists from an outpatient setting participated in a six-week, within-subject study that used an alternating treatments design (ABCABC) which was created via a participatory approach where participants actively engaged in the planning of the study. Imagination- (B) and VR-based (C) relaxation interventions alternated weekly with baseline weeks (A) in between. The VR environments were tailored to participants' preferences through generative AI.ResultsRelaxation consistently increased in both conditions based on self-report and physiological (skin conductance levels) measures. Burnout and stress did not significantly decrease over time and VR did not yield significantly greater effects on all outcomes. Imagery ability was not associated with greater relaxation, whereas presence showed a positive correlation in one VR session.ConclusionThese findings suggest that brief imagination and VR interventions can enhance relaxation in psychotherapists. The lack of significant differences between conditions suggests that VR does not inherently outperform traditional methods, especially with participants already familiar with imagination exercises.